2014
DOI: 10.3802/jgo.2014.25.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Condom and oral contraceptive use and risk of cervical intraepithelial neoplasia in Australian women

Abstract: ObjectiveTo assess the association between condom use and oral contraceptive consumption and the risk of cervical intraepithelial neoplasia (CIN).MethodsA cross-sectional study was conducted in Perth clinics. A total of 348 women responded to the structured questionnaire. Information sought included demographic and lifestyle characteristics such as the use of condom for contraception, consumption of oral contraceptive, and duration of oral contraceptive usage. Crude and adjusted odds ratio (OR) and associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…Duration of each hormonal contraceptive usage still needs to be examined. 12 The number of active family planning participants from 2014 to 2016 showed an upward year-to-year trend. The percentage of active family planning participants who used hormonal contraceptives ranged from 81.58% to 81.97% (injectables, 47.54%; pills, 23.58%; implants, 10.46%).…”
Section: Introductionmentioning
confidence: 99%
“…Duration of each hormonal contraceptive usage still needs to be examined. 12 The number of active family planning participants from 2014 to 2016 showed an upward year-to-year trend. The percentage of active family planning participants who used hormonal contraceptives ranged from 81.58% to 81.97% (injectables, 47.54%; pills, 23.58%; implants, 10.46%).…”
Section: Introductionmentioning
confidence: 99%
“…However, the World Health Organization did not recommend stopping the oral contraceptives use because it outweigh its risk [9] . Indeed, there is lack in evidence on the relationship between the use of oral contraceptive pills and the risk of cervical intra-epithelial neoplasia [10] and therefore, the present study aims to investigate whether the use of combined oral contraceptive pills is associated with any risk or not.…”
Section: Introductionmentioning
confidence: 99%
“…Over 35% of the cases had positive history of using oral contraceptive pills. Although earlier studies showed that there might be a significant correlation between abnormal Pap smear findings and hormonal contraception (19), yet a more recent Australian cross-sectional study documented that the duration of oral contraceptive use among women with Pap smear changes consistent with CIN was significantly shorter than those without abnormalities; indicating that oral contraceptives could be inversely associated with CIN (20). The value of Pap smears in detecting cellular abnormalities has been well documented in the literature as the most successful screening tool for cervical cancer; specifically when applied together with Colposcopy and HPV tests (3,(11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 96%